Expression and clinical significance of SUMO-specific protease 1 in breast cancer - Xiaofang FENG; Yuxuan WANG; Huijie XU; Qi LIU; Wugang LIU; Maoyuan ZHU; Xi DENG; Kai QIN; Qiyan ZENG (Guangxi Yike Daxue xuebao)
Objective To investigate the expression and its clinical significance of small ubiquitin-like modifier (SUMO/sentrin) -specific protease 1 (SENP1) in breast cancer tissues. Methods First, the UALCAN database was utilized to analyze the SENP1 expression levels in breast cancer patients. Subsequently, reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was employed to examine the expression levels of SENP1 in different breast cell lines and 44 cases of breast cancer tissues, and explore its correlation with clinicopathological parameters. Meanwhile, immunohistochemical analysis was performed to assess protein expression levels of SENP1 in breast cancer tissues. Finally, immune infiltration analysis was conducted to analyze the relationship between SENP1 and immune cell infiltration. Results UALCAN database analysis revealed significantly upregulated SENP1 expression in breast cancer tissues (P < 0.05). The expression of SENP1 was markedly elevated in MDA-MB-231, MCF7, and HCC1937 cell lines as well as breast cancer tissues (P < 0.05). The SENP1 levels in patients with high levels of Ki-67 was significantly higher than those in patients with lower levels of Ki-67 (P < 0.05). SENP1 levels in patients with histological grade Ⅲ were significantly higher than those in patients with histological grade Ⅱ (P < 0.05); SENP1 levels were positively correlated with serum progesterone levels (P < 0.05). Bioinformatics analysis revealed that the infiltration of 10 types of immune cells, such as dendritic cells, was significantly decreased in patients with higher levels of SENP1 (P < 0.05), while the infiltration of other 3 types of immune cells such as T helper cells, was significantly increased (P < 0.05). Conclusion The expression of SENP1 is significantly upregulated in breast cancer tissues, which may promote the development of breast cancer by inhibiting immune cell infiltration.